Astronium graveolens tree – mineral exploration guide in search for copper and potential use of this plant for reforestation of mining waste - Lutyński, Piotr; Pieczonka, Jadwiga; Piestrzynski, Adam; Mosquera-Palacios, Marvin; Del Castillo-Londoño, Alma Cristina (Geology, Geophysics and Environment, 2023)
Geological mapping and sampling of sediment-hosted copper-silver mineralization in NE Colombia identified the association of the Astronium graveolens tree (Diomate Gusanero) with the elevated presence of copper (up to 317 ppm) and silver (up to 24 ppm) in plant ash. During the dry season, when most plants lose their leaves, young Astronium graveolens seedlings growing along copper sulfide-rich showings retain their green foliage. This observation allowed authors to effectively use this plant as an exploration guide in search for copper mineralization and Astronium graveolens can be potentially considered as a geobotanical indicator plant. The observed resistance of Astronium graveolens to the presence of copper sulfides suggests that this tree could be also a potential excellent species for reforestation and reclamation of tailings and other mining waste.